Pengaruh Konsentrasi Paklobutrazol dan Dosis Pupuk ZA Plus Terhadap Pertumbuhan dan Hasil Tanaman Jagung Pulut (Zea mays ceratina L.) Varietas Rasanya F1 - Adiyoga, Jessica Putri; Sulistyono, Agus; Djarwatiningsih, Djarwatiningsih (Jurnal Agroekoteknologi, 2025)
Pulut corn (Zea mays ceratina L.) has high economic potential but its productivity is still low. This study aimed to evaluate the effect of a combination of paklobutrazol concentration and ZA Plus fertilizer dosage on the growth and yield of pulut corn. A factorial experiment with a Randomized Block Design was conducted in Gresik with four concentrations of paklobutrazol (0, 1250, 1500, 1750 ppm) and four doses of ZA Plus fertilizer (450, 750, 1000, 1250 kg/ha). Results showed that the treatment combination significantly affected plant length, cob diameter, and sugar content, while cob weight per plant and per hectare were not significantly different. The highest plant length was obtained without paklobutrazol and 1250 kg/ha dose of ZA Plus fertilizer, while the largest cob diameter was obtained in the combination of 1250 ppm paklobutrazol and 1250 kg/ha ZA Plus fertilizer. ZA Plus fertilizer also significantly increased the sugar content of pulut corn. This study concludes that proper application of paklobutrazol and ZA Plus fertilizer can improve the growth and quality of pulut corn.